2009
DOI: 10.1242/jeb.023036
|View full text |Cite
|
Sign up to set email alerts
|

Smelling the difference: controversial ideas in insect olfaction

Abstract: SummaryIn animals, the sense of smell is often used as a powerful way to attract potential mates, to find food and to explore the environment. Different animals evolved different systems to detect volatile odorants, tuned to the specific needs of each species. Vertebrates and nematodes have been used extensively as models to study the mechanisms of olfaction: the molecular players are olfactory receptors (ORs) expressed in olfactory sensory neurons (OSNs) where they bind to volatile chemicals, acting as the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…Although the identity of the slower migrating species as dimers requires formal demonstration, we note that there have been numerous reports concerning the presence of SDS-resistant dimers for a variety of other receptors [45], [46], [47], mostly GPCRs for which it is well established that they function as dimers and/or higher order oligomers [60]. Moreover, as has also been pointed out previously [61], insect ORs are likely to undergo post-translational modifications that could affect many of their properties including stability, expression levels and internalization. Although a combination of approaches will be required for confirmation and interpretation of any results obtained, including the detected differences in expression levels between OR1 and OR2, which was consistently observed with different constructs, heterologous expression of insect ORs in cell culture systems, such as the one used in the present study, could prove to represent important tools for the dissection of the totally unexplored area of post-translational processing.…”
Section: Discussionsupporting
confidence: 73%
“…Although the identity of the slower migrating species as dimers requires formal demonstration, we note that there have been numerous reports concerning the presence of SDS-resistant dimers for a variety of other receptors [45], [46], [47], mostly GPCRs for which it is well established that they function as dimers and/or higher order oligomers [60]. Moreover, as has also been pointed out previously [61], insect ORs are likely to undergo post-translational modifications that could affect many of their properties including stability, expression levels and internalization. Although a combination of approaches will be required for confirmation and interpretation of any results obtained, including the detected differences in expression levels between OR1 and OR2, which was consistently observed with different constructs, heterologous expression of insect ORs in cell culture systems, such as the one used in the present study, could prove to represent important tools for the dissection of the totally unexplored area of post-translational processing.…”
Section: Discussionsupporting
confidence: 73%
“…However, later studies indicated that they possess a distinct 7TM topology with the amino terminus located at the intracellular side, and function as heteromeric ligand-gated ion-channels (Sato et al, 2008;Smart et al, 2008;Wicher et al, 2008). Therefore, the involvement of G proteins in insect olfactory signal transduction is still under question (Pellegrino and Nakagawa, 2009). These sequences were not further analyzed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent investigations into the molecular mechanisms of chemosensory signalling have revealed an unexpected dichotomy: mammals (and vertebrates in general) almost exclusively use metabotropic chemosensory receptors—that is, the ligand‐binding receptors indirectly activate ion channels through second messengers—whereas insects (and possibly all arthropods) might predominantly use ionotropic mechanisms, in which the primary chemosensory receptors are ligand‐gated ion channels (Pellegrino & Nakagawa, 2009; Spehr & Munger, 2009; Touhara & Vosshall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the involvement of G proteins and second messengers downstream from insect ORs has been studied intensively over the past decade, their contribution to odour sensing remains unclear, and in vivo they might have a principally modulatory role. These issues have been discussed in detail elsewhere (Benton, 2008; Nakagawa & Vosshall, 2009; Pellegrino & Nakagawa, 2009; Ronderos & Smith, 2009). Little is known about how GRs transduce signals, but their homology to ORs makes it plausible that these receptors also function as ion channels.…”
Section: Introductionmentioning
confidence: 99%